Migration from Ukraine to the Czech Republic with respect to the war conflict in Eastern Ukraine - Zdeněk Uherek (University of Warsaw, Centre of Migration Research (CMR), 2016)
The paper focuses on changes in migration from Ukraine to the Czech Republic as a result of the war events in East Ukraine especially in 2014-2015. It briefly summarises Ukrainian- Czech migration history and then concentrates upon non-asylum migration with respect to the events in Ukraine since 2014, the area of international protection and the migration of Czech compatriots from Ukraine to the Czech Republic. The article concludes that up to 2016 the armed conflict in Ukraine, despite its seriousness and destabilising consequences, did not distinctly effect changes in the migration situation in the Czech Republic, although the statistical data show increasing interest among Ukrainian citizens in permanent stay permits in the Czech Republic, acquisition of Czech citizenship and refugee status. Since 2015 Czech institutions have also assisted several hundred descendants of 19th-century settlers to Ukraine in moving to the Czech Republic. Despite these developments, at present, the overall numbers of incomers from Ukraine to the Czech Republic are predominantly influenced by economic contexts. Rather than migration, the citizens of Ukraine in the Czech Republic, members of the Ukrainian minority in the Czech Republic and the Czech compatriots in Ukraine reacted to the military situation in the form of social activities. To describe the situation, statistical sources are used in particular, while the paper does not cover short-term and illegal migrations.
Keywords: 330; Ukraine; Czech Republic; migration; resettlement